ANALYSIS OF FINANCIAL BEHAVIOR AND INCOME ON INVESTMENT DECISIONS OF MSME ACTORS IN THE CULINARY SECTOR IN SUTERA SUBDISTRICT, SOUTH COAST REGENCY - Yustrifa Anella; Elsa Meirina; Dewi Zulfia; Anggi Saputra (Kajian Akuntansi, 2026)
This study aims to analyze the effect of financial behavior and income on investment decisions of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Sutera District, Pesisir Selatan Regency. This research uses a quantitative method with a multiple linear regression approach. The population of this study consists of 387 MSME actors, with a sample of 90 respondents selected using convenience sampling. The data used are primary data obtained through questionnaires. The results show that financial behavior and income each have a positive and significant effect on investment decisions. In addition, both variables simultaneously have a significant effect on investment decisions of MSMEs in the culinary sector in Sutera District.